A 14th-Century Sculpted Arcade from Coverham Abbey. (1st September 2013) - Harrison, Stuart
Abstract : The discovery of several sections of a trefoiled arcade of 14th-century date at Coverham abbey is a major addition to sculpture from the English Premonstratensian houses. Discovered in a robber trench whilst resurfacing a courtyard, they can be linked to a panel reused in the gable of the Georgian house. When reconstructed, they show a trefoiled arcade with sculpted spandrels in the form of human figures. Positive identification of the figures is difficult, and they could be of Christ or apostles. While the arcade looks to have been part of a cloister arcade, there is the possibility that it formed part of the abbey laver, flanking the refectory doorway.